Segregation and pattern formation in dilute granular media under microgravity conditions - Eric Opsomer; Martial Noirhomme; Nicolas Vandewalle; Eric Falcon; Simon Merminod (npj Microgravity, 2017)
Space exploration and exploitation face a major challenge: the handling of granular materials in low-gravity environments. Indeed, grains behave quite differently in space than on Earth, and the dissipative nature of the collisions between solid particles leads to clustering. Within poly-disperse materials, the question of segregation is highly relevant but has not been addressed so far in microgravity. From parabolic flight experiments on dilute binary granular media, we show that clustering can trigger a segregation mechanism, and we observe, for the first time, the formation of layered structures in the bulk.